The Correlation Between CYP19 Levels, VAS of Dysmenorrhea, and the Grading Score ASRM of Endometriosis - Fatimah Usman; Muhammad Komarul Hakim; Heriyadi Manan; Mgs. Irsan Saleh (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Objective: We aim to assess the correlation between the CYP19 level, the visual analogue scale (VAS) pain and endometriosis American Society for Reproductive Medicine (ASRM) grading scale.Method: An observational analytic study with a cross–sectional design was conducted at the Obstetrics/Gynecology Department, RSUP Dr. Moh Hoesin Palembang, Laboratory of Biomedical and Biomolecular of the Faculty of Medicine, Universitas Sriwijaya from July–December 2022. Subjects who were diagnosed with endometriosis and met the inclusion and exclusion criteria underwent a histopathological examination to measure the degree of disease according to ASRM. Using the same sample, the CYP19 levels were assessed by enzyme linked immunosorbent assay (ELISA). Univariate and bivariate statistical analyses were performed to see the correlation.Results: This study involved 37 subjects aged 20–48 (Mean: 32 years). We found there was a significant correlation between the degree of VAS score and ASRM grading (p<0.001). In addition, although CYP19 expression was found in ectopic endometrial tissue, there was no significant correlation between the level of CYP19 expression in the tissue and the VAS score dysmenorrhea (p= 0,618) and ASRM grading (p=0.604).Conclusion: There is no significant correlation between CYP19 levels and the degree of pain in VAS or ASRM grading in patients.Hubungan Kadar CYP19, Visual Analogue Score (VAS) Dismenorea, dan Grading Score American Society for Reproductive Medicine (ASRM) Endometriosis Abstrak Tujuan: Penelitian ini bertujuan untuk menilai hubungan kadar CYP19, skala nyeri visual analogue scale (VAS) dan grading berdasarkan American Society for Reproductive Medicine (ASRM) pada pasien endometriosis.Metode: Sebuah studi analitik observasional dengan rancangan cross–sectional dilakukan di Bagian/KSM Obstetri Ginekologi, RSUP Dr. Moh Hoesin Palembang dan Laboratorium Biomedis dan Biomolekuler Fakultas Kedokteran Universitas Sriwijaya, pada periode Juli–Desember 2022. Subjek penelitian yang terdiagnosis endometriosis dan memenuhi kriteria inklusi dan eksklusi, dilanjutkan pemeriksaan histopatologis untuk mengukur derajat penyakit sesuai rASRM. Dengan menggunakan sampel yang sama dilakukan penilaian kadar CYP19 melalui pemeriksaan enzyme linked immunosorbent assay (ELISA). Analisis statistik univariat dan bivariat dilakukan untuk melihat hubungan tersebut. Hasil: Penelitian ini melibatkan 37 subjek dengan rentang usia 20–48 (Median: 32 tahun). Pada penelitian, terdapat hubungan yang bermakna antara derajat nyeri VAS endometriosis terhadap derajat endometriosis (p<0,001). Selain itu, walaupun ditemukan adanya ekspresi CYP19 pada jaringan endometrium ektopik, namun tidak terdapat hubungan yang bermakna antara tingkat kadar CYP19 pada jaringan dengan derajat VAS score dismenorea (p=0,618) dan derajat ASRM endometriosis (p=0,604).Kesimpulan: Tidak terdapat hubungan bermakna antara kadar CYP19 dengan derajat nyeri VAS maupun derajat ASRM endometriosis pada pasien.Kata kunci: ASRM, Kadar CYP19, Endometriosis